Physical and Spiritual Dimensions of Happiness in the Thought of al-Fārābī and Ibn Sīnā - Mukhammad Zamzami; Abdullah HosseiniEskandian; Hossein Gholizadeh; Mohammad Moradi Shariati; Muktafi Muktafi; Abd A'la (Teosofia: Indonesian Journal of Islamic Mysticism, 2021)
The most important goal in human life is to achieve happiness, and because people are subject to certain ideas and beliefs and have a different system of thought, it has led to different interpretations of happiness. If the Sufis interpret happiness around the orbit of inner happiness in the soul, not related to material achievements such as money, children, prestige, offspring, and others, then this is different from the interpretation of the happiness of two Muslim philosophers, Ibn Sīnā and al-Fārābī. In this article, with a descriptive-analytical method and using library resources, we first try to study the lexicon of the word happiness and the views of other thinkers in this regard, in the following, what are happiness, the levels of happiness, and the classification of happiness in the intellectual system of Ibn Sīnā and al-Fārābī. Happiness in Ibn Sīnā and al-Fārābī's thought is the same concern of human perfectionism from the beginning of creation, and this has caused these two philosophers to discuss this in their different works, and both philosophers do not know human happiness as anything other than reaching God and His pleasure.